POTENSI TANIN DARI HUTAN PAYAU TARAKAN, KALIMANTAN TIMUR - Suwardi Sumadiwangsa; Yacob Ando (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
Mangrove forest grows widely distributed throughout Indonesia, and one of the most promising resource is in East Kalimantan.Until recently the utilization of mangrove forest is only for wood, while the bark is wasted, although various literatures have indicated that the tanning material found in the bark can be a intesfactory component for glue manufacture.This paper presents a survey result on the standing stock of 11 mangrove species at the Forest District of Bulongan in East Kalimantan. The survey was based on a 25% sampling intensity which is jointly conducted both by PT Karyasa Kencana and District of Forestry at Bulongan, East Kalimantan. The tannin content of the bark were determined at the Forest Product Research and Development Centre Laboratory in Bogor. In this Province, the mayor tannin producing mangroves are Bruguiera caryophylloides, Rhizophora macronata, and Bruguiera gymnorrhiza.